Immunoreactivities to α-SMA and S-100 proteins in the testis of the African four-toed Hedgehog (Atelerix albiventris) (2020)
The African four-toed hedgehog is a small nocturnal mammal, characterized by a short-grooved brown or grey spine covering the dorsum of the body with a band of whitish fur running across their forehead, little is known about the reproductive biology of this animal. The present study aimed to evaluating the validity of immunohistochemistry in the differential labelling of the different cellular components of the testis of the African four-toed hedgehog. Paraffin-embedded testicular sections were stained by conventional histological technique using ten male African four-toed hedgehogs captured from the wild animals in Ibadan, Nigeria. Primary antibodies against alpha smooth muscle actin (α-SMA) and S-100 were applied on paraffin sections. The peritubular myoid cells, the testicular capsule and vascular endothelium expressed strong immunostaining for α-SMA. The spermatogenic cells, Sertoli and Leydig cells, peritubular myoid cells, the testicular capsule, straight tubules as well as rete testis and vascular endothelium all expressed positive immunostaining for S-100. α-SMA and S-100 proteins play active roles in cytoskeletal physiology of testis of the African four-toed hedgehog while S-100 protein plays additional role in the structural formation and maintenance of the blood-testis barrier during the process of spermatogenesis in the animal. It is concluded that α-SMA and S-100 proteins has active roles in the cytoskeletal structure of testis and physiology of the African four-toed hedgehogs.